Electrical and optical properties of nanostructured titanium dioxide (TiO2) thin films annealed at different temperatures: article / Mohd Azli Abdulah - Abdulah, Mohd Azli (2009)
Nanostructured Titanium Dioxide (TiO2) thin film has been synthesized using sol-gel method and deposited onto glass substrates using spin coating technique. These thin films then annealed at various temperatures. The electrical, optical and structural characterizations of the as deposited and annealed films were carried out using IV measurement with 4point probe equipment, UV-Vis spectroscopy, atomic force microscopy (AFM) and scanning electron microscopy (SEM). From this study, it is known that, electrical properties were influenced by changes of annealing temperature. Resistivity of thin films was found to decrease as the annealing temperatures increase. Based on the readings from UV-Vis spectroscopy, it is found that transmittance properties spectroscopy, AFM and SEM. All the results were gathered and finally this paper was written. 2. Objectives The purpose of this research is to investigate the electrical properties of nanostructured TiO2 annealed at different temperatures. The specific objectives of this research are: 1. To deposit the transparent nanostructured TiO2 on glass substrates by using spin coating method of TiO2 thin films increased as annealing temperatures increase. This result is supported by surface topography and morphology of the thin films which indicate grains size increasing as temperature increases.